An investigation into the spiritual needs of neuro-oncology patients from a nurse perspective - Nixon, Aline Victoria; Narayanasamy, Aru; Penny, Vivian (BioMed Central, 2013)
Background: Spiritual needs of cancer patients should be assessed and discussed by healthcare professionals. Neurosurgical nurses need to be able to assess and support neuro-oncology patients with their spiritual needs from diagnosis and throughout their hospital stay.